2021
DOI: 10.1017/s1049096520001754
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Fieldwork: Challenges and Solutions

Abstract: This reflection article presents insights on conducting fieldwork during and after COVID-19 from a diverse collection of political scientists—from department heads to graduate students based at public and private universities in the United States and abroad. Many of them contributed to a newly published volume, Stories from the Field: A Guide to Navigating Fieldwork in Political Science (Krause and Szekely 2020). As in the book, these contributors draw on their years of experience in the field to identify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 1 publication
1
22
0
Order By: Relevance
“…On the other hand, the lack of studies on GD in LAC identified in this review and global reviews on GD demonstrates the limited evidence available on this problem in the region and the need to develop further studies. A potential reason for why new studies on the prevalence of GD in LAC and other regions of the world have not been conducted could be attributed to the COVID-19 pandemic, which reoriented the development of research in the generation of knowledge about this disease, reducing and limiting the development of research in other health topics as well [ 55 ]. Several authors discussed the relevance and implications of the inclusion of GD within the ICD-11 diagnoses in the last two years [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the lack of studies on GD in LAC identified in this review and global reviews on GD demonstrates the limited evidence available on this problem in the region and the need to develop further studies. A potential reason for why new studies on the prevalence of GD in LAC and other regions of the world have not been conducted could be attributed to the COVID-19 pandemic, which reoriented the development of research in the generation of knowledge about this disease, reducing and limiting the development of research in other health topics as well [ 55 ]. Several authors discussed the relevance and implications of the inclusion of GD within the ICD-11 diagnoses in the last two years [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Innovations in sourcing quality data about tourism‐dependent communities' experiences were necessary. Similar to other social scientists having to adapt to the pandemic circumstances, we came up with practical solutions to conducting fieldwork remotely (Krause et al ., 2021 ). Our plan for data collection involved three key components.…”
Section: Methods: Adaptive Research In Practicementioning
confidence: 99%
“…2 Researching informality in times of Covid-19 in Lahore Globally, the most common adaptations, or methodological 'fixes' in conducting research during the pandemic, have been phone interviews and online surveys, which have defined much of the work published in 2020 and 2021, as well as some adaptations to conduct qualitative and ethnographic research mediated by technology (Hall, Gaved and Sargent 2021;Howard and Roberts 2020;Howlett 2021;Krause et al 2021;Reñosa et al 2021). These adaptations have ensured the continuity of research efforts during a time when the world was essentially 'closed for business' -thereby enabling critical insights into how people were faring at this unprecedented time and capturing the ways in which their lives and livelihoods were being impacted by the pandemic and state responses to the pandemic.…”
Section: Ids Bulletinmentioning
confidence: 99%
“…Our ability to do in-person interviews during the pandemic thus depended on three critical factors. First, we had to remain flexible as to how we were going to do this research, recognising, as have most researchers during this time, the need for contingency planning and that the best laid plans might mean little in the field (Krause et al 2021). Second, we worked closely with NGOs both to identify respondents in the informal sector and to understand how to ensure their safety and comfort during the pandemic.…”
Section: Ids Bulletinmentioning
confidence: 99%